Pengembangan Produk Inovasi Pengharum Mobil Berbasis Nilam Berdasarkan Respon Pelanggan dan Analisis SWOT - Raihan Dara Lufika; Friesca Erwan; Sanusi Iswandi; Al Hilal Bakri; Ayi Wahyuni; Della Ayu Nadia; Wilda Diva Kartika; Syaifullah Muhammad; Elly Sufriadi; Ernawati Ernawati (Jurnal Teknologi dan Industri Pertanian Indonesia, 2023)
This study aims to observe customer's responses toward car fragrance products, examine the volatility and properness of the essential oil-based product. Essential oil is a group of vegetable oil in form of liquid that easily evaporated at room temperature. Hence it gives unique scents. This research is carried out with a descriptive method using a qualitative approach. The data analysis technique of this research is using SWOT analysis (Strength, Weakness, Opportunity, and Threat) and calculation of Cost of Goods Sold to compare the two samples of car freshener. The result of this research showed that product A which is based on patchouli essential oil, citronella, coffee, and gadenza essential was more preferable by the customer with the range of selling price in IDR 19.000 – IDR 22.000 than product B. SWOT analysis explained that the product's strength is the multifunction of the product as aromatherapy and the opportunity of the product to compete in a wider market; while the weakness of the product is the high labour of production process. The total calculation of the Cost of Goods Sold for product A is IDR 15.440 and product B is IDR 15.960.